Overparenting and Emerging Adults' Insecure Attachment With Parents and Romantic Partners. Issue 3 (June 2022) - Jiao, Jian; Segrin, Chris
Attachment theory articulates that social and personal interactions influence individuals' attachment characteristics. Although research has revealed various negative consequences of overparenting among offspring, very few studies have looked at the attachment features of overparented emerging adults. Relying on cross-sectional data collected from 231 emerging adults ( M age = 24.22 years, 57.1% females) recruited from Amazon's Mechanical Turk (MTurk), the present study examined the associations between overparenting and emerging adults' insecure attachment (i.e., attachment anxiety and/or avoidance) in parent-offspring and romantic contexts, and if overparented emerging adults delay marriages. Results showed that overparenting was robustly associated with emerging adults' insecure attachment with both parents and romantic partners, and overparented emerging adults were less likely to be married. Overall, the findings suggest that overparenting practices, although seemingly well-intentioned, might indeed create barriers for emerging adults to develop and maintain positive and healthy relationships.